Pola Dakwah dan Peran Lembaga Dakwah Nahdlatul Ulama (LDNU) dalam Internalisasi Nilai-Nilai Islam pada Masyarakat Kota Semarang - Sulistiani, Putri Fatimah; Asyifa’, Fadhlu Izza; Suprihatiningsih, Suprihatiningsih (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2026)
The LDNU responds to the challenges posed by Semarang’s heterogeneous and dynamic urban society through its da’wah approach and its role in helping to internalize Islamic values within the community. This study aims to analyze the da’wah patterns and the role of the Nahdlatul Ulama Da’wah Institute (LDNU) in internalizing Islamic values within the community of Semarang City. The research method employs a descriptive qualitative approach using library research techniques, involving the collection of data from scientific journals, books, and official documents analyzed thematically. The results of the study indicate that LDNU implements four primary patterns of da’wah: the inclusive pattern, the cultural and traditional pattern, the structural and institutional pattern, and the digital pattern. These are effective in strengthening religious values, enhancing spiritual awareness, and maintaining social harmony in urban communities. Consequently, LDNU plays a crucial role in shaping a religious, tolerant, and morally upright society. In conclusion, LDNU holds a strong position as a driving force for Islamic da’wah in the internalization of Islamic values amidst the dynamics of modern life in the city of Semarang.